2016
DOI: 10.1128/jvi.01084-16
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Chromatin-Tethering Domain of Murine Leukemia Virus p12

Abstract: Murine leukemia virus (MLV) p12, encoded within Gag, binds the viral preintegration complex (PIC) to the mitotic chromatin. This acts to anchor the viral PIC in the nucleus as the nuclear envelope re-forms postmitosis. Mutations within the p12 C terminus (p12 PM13 to PM15) block early stages in viral replication. Within the p12 PM13 region (p12 60 PSPMA 65 ), our studies indicated that chromatin tethering was not detected when the wild-type (WT) p12 protein (M63) was expressed as a green fluorescent protein (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…In addition to the PPPY motif's function in late domain budding, recent findings show that the p12 N-terminal 25 DLLTEDPP PY 34 motif is a repressor of the p12 C-terminal chromatin binding motif, suggesting that these two motifs are binding during infection (26). This dual function for the PPPY motif is supported by previous research indicating that it had both early and late defects in replication (1).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In addition to the PPPY motif's function in late domain budding, recent findings show that the p12 N-terminal 25 DLLTEDPP PY 34 motif is a repressor of the p12 C-terminal chromatin binding motif, suggesting that these two motifs are binding during infection (26). This dual function for the PPPY motif is supported by previous research indicating that it had both early and late defects in replication (1).…”
Section: Discussionsupporting
confidence: 66%
“…Phosphorylation of p12 can act directly through activating a tethering competent conformation or indirectly through releasing a repression domain. Deletion studies of p12 indicated that the N terminus of p12 acts as a repression domain of tethering (26). The role of phosphorylation to regulate tethering was examined with the minimal tethering domain 61 SPMASRLRGRR 71 -GFP fusion protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the NSD3 ET binding motif is flanked by lowcomplexity regions [DisMeta, (Huang et al, 2014)], including a Pro-rich sequence N-terminal to the ETBM (Supplementary Figure S4), that are predicted to be intrinsically-disordered. Recently it was proposed that BET proteins interact with MLV IN after p12-mediated nuclear retention of the viral PIC (Brzezinski et al, 2016a, Brzezinski et al, 2016b, Borrenberghs et al, 2019. Using FRET-based studies, the interaction of BET proteins with MLV IN was shown to cause alteration in the quaternary structure of IN within the PIC (Borrenberghs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During MLV infection, the viral integrase associates with the reversetranscribed viral DNA as part of a nucleoprotein complex called the pre-integration complex (PIC), which also contains other viral proteins including p12 and capsid (CA), along with host proteins including barrier-to-autointegration factor (BAF) (Prizan-Ravid et al, 2010, Fassati and Goff, 1999, Lee and Craigie, 1998. The p12 protein tethers the PIC to mitotic chromatin and ensures nuclear retention through chromatin tethering (Brzezinski et al, 2016b, Elis et al, 2012, Schneider et al, 2013, Wight et al, 2012. However, subsequent interaction with BET proteins is an important determinant for genomic targeting of the PIC towards transcription start sites (TSS) and CpG islands (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%